AUGMENTING GROUND WATER RESOURCE THROUGH INTERGRATED WATERSHED MANAGEMENT - Sastry, G.; Ojasvi, P.R.; Goel, P.K.; Samra, J.S. (Journal of Soil and Water Conservation, 2022)
In certain regions of the country, exploitation of ground water is far in excess of net annual recharge from the natural process. Soil and water conservation measures, though, not primarily designed for artificial aquifer recharge but add on to recharge process. Prevailing engineering practices that have been found suitable for artificial recharge to augment depleting ground water aquifers are discussed in this paper. The impact of soil and water conservation measures adopted on watershed basis by CSWCRTI, Dehradun and its regional research centers on development of ground water resources and subsequent recharge is also presented in this paper.